Past debates, fresh impact on nano-enabled food : a multigroup comparison of presumed media influence model based on spillover effects of attitude toward genetically modified food - Ho, Shirley S. (2020)
Informed by the notion of spillover effects between two phenomena, this study examines how differences in prior attitudes would influence the relationships posited by the influence of presumed media influence (IPMI) model. Specifically, this study examines how pre-existing favorable and unfavorable attitudes toward genetically modified (GM) food are associated with audiences’ intention to consume nano-enabled food. The results of a nationally representative survey with 1,000 respondents found general support for the IPMI from media attention to behavioral intentions, through attitude and social norms. Further, a multigroup analysis of the IPMI provided evidence for differences in the IPMI effects between the audiences with favorable and unfavorable pre-existing attitudes toward GM food. These results contribute to a stronger theoretical understanding of the IPMI in terms of how pre-existing attitudes toward a preceding food technology can have a spillover effect on how audiences make decisions regarding a newer food technology.